Formation and characterization of glutathione adducts derived from polybrominated diphenyl ethers. (February 2015) - Huang, Lihua; Lai, Yongquan; Li, Charlie; Qiu, Bin; Cai, Zongwei
Highlights: Twenty PBDE-GSH adducts were synthesized, separated and analyzed by LC-MS. Formation mechanism of the PBDE-GSH adducts was proposed and discussed. MS/MS fragmentation pathways of the PBDE-GSH adducts were proposed. The stability of PBDE-GSH adducts were measured and discussed. Formation of GSH-PBDEs adducts may provide valuable information for toxicology study on PBDEs and OH-PBDEs. Abstract: The reactions of glutathione (GSH) with polybrominated diphenyl ethers (PBDEs) quinones with different degrees of bromination on the PBDEs ring were studied. Liquid chromatography coupled with mass spectrometric (LC-MS) analysis showed that four types of adducts were formed from the reaction of each PBDEs quinone (PBDE-Q) with GSH. The proposed reaction pathway was confirmed using ion trap-MS/MS technique. Our results demonstrate that adduct-1 was formed following the Michael Addition, a reaction of the sulfhydryl group from GSH with electron deficient carbon from PBDEs-Q ring. Compared with other carbons on the quinone ring, carbon in position 6 has a smaller steric hindrance, thus the addition reaction is likely to occur in that position. Hydrated quinone-GSH adduct-1 is easily oxidized to generate an adduct-2 in an aqueous solution. Substitution reaction from bromine atom on adduct-2 quinone ring with sulfhydryl group from GSH further generates adduct-3 that is unstable and can be readily hydrolyzed to adduct-4 in aqueous solution. Both adduct-1 and adduct-4 were unstable as well, immediately oxidized to adduct-2 and adduct-3 in the air, respectively. The results reveal that brominated quinones undergo a rapid non-enzymatic debromination upon reaction with GSH, and open a new view for our understanding on mechanism of metabolism and the toxicity of this class of compounds.